2021
DOI: 10.1007/s00170-021-07625-y
|View full text |Cite
|
Sign up to set email alerts
|

Process characterization and analysis of ceramic powder bed fusion

Abstract: Powder bed fusion (PBF) of ceramics is often limited because of the low absorptance of ceramic powders and lack of process understanding. These challenges have been addressed through a co-development of customized ceramic powders and laser process capabilities. The starting powder is made of a mix of pure alumina powder and alumina granules, to which a metal oxide dopant is added to increase absorptance. The performance of different granules and process parameters depends on a large number of influencing facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…For lower energy densities, the molten phase front remains in contact with the powder and for very low power the laser interacts directly with the powder (Supplementary Movies 1 and 2 for 3.35 W and 4.3 W). A similar effect was observed by Florio et al 59 using a high speed camera. Here, the energy density was varied by changing laser scanning speed, while keeping a constant laser power.…”
Section: Effect Of Laser Power On Powder Denudationsupporting
confidence: 85%
See 1 more Smart Citation
“…For lower energy densities, the molten phase front remains in contact with the powder and for very low power the laser interacts directly with the powder (Supplementary Movies 1 and 2 for 3.35 W and 4.3 W). A similar effect was observed by Florio et al 59 using a high speed camera. Here, the energy density was varied by changing laser scanning speed, while keeping a constant laser power.…”
Section: Effect Of Laser Power On Powder Denudationsupporting
confidence: 85%
“…The typically used laser scanning speeds during LPBF of ceramics are in range from 1 to 100 mm/s 10,15,19,59 . For this range, the achievable tomogram rate is already compatible with typical laser velocities for ceramics, as for instance for 10 mm/s laser scanning speed and acquisition with 1000 tps, the laser spot would move by 10 µm during acquisition of one tomogram.…”
Section: Introductionmentioning
confidence: 99%
“…The use of PBF processes is limited for ceramics, because most ceramic powders have low absorptance [43]. However, some authors have worked in this area; for example, Juste et al, who obtained oxide ceramic parts with the SLM technology [44].…”
Section: Powder Bed Fusion (Pbf)mentioning
confidence: 99%
“…Scope of this review for the dAM of ceramic oxides. Image sources from [24][25][26][27][28][29][30][31][32][33][34][35]. Adapted from [24], with permission from Springer Nature.…”
Section: Dam Techniquesmentioning
confidence: 99%
“…Consequently, high relative density up to 99.6% can be achieved for r-GO doped ceramics at lower laser energy input, as compared to the carbon-doped ones. Other than carbon-based materials, Pfeiffer et al [65,66] and Florio et al [26,30] reported an absorption enhancement by incorporating colored oxide nanoparticles into raw Al 2 O 3 powders, such as Fe 2 O 3 and MnO 2 . They achieved an absorption rate of 90%, leading to a relative density exceeding 98% for the as-printed components.…”
Section: Zhang and Modestmentioning
confidence: 99%